Cognitive Differences between Men and Women who Fracture their Hip and Impact on Six‐Month Survival. Issue 3 (8th February 2017) - Gruber‐Baldini, Ann L.; Hosseini, Mina; Orwig, Denise; Grattan, Lynn; Chiles Shaffer, Nancy; Hochberg, Marc; Magaziner, Jay
Abstract : Objectives: There is limited research in cognition and its relationship to mortality after hip fracture among men compared to women. Therefore, the goals of this study were to: (1) compare men and women who fractured their hip on cognition after hospital discharge, and (2) examine the impact of cognition on the differential risk of 6‐month mortality between men and women post fracture. Design: Prospective cohort study. Setting: Eight hospitals in Baltimore, Maryland. Participants: Frequency matched 168 male and 171 female hip fracture patients, ages 65 or older, living in the community before fracture. Measurements: Cognition assed by Modified Mini‐Mental State Examination (3MS, and derived MMSE score), Hooper Visual Organization test (HVOT), and Trail‐making test (Trails A & B) within 22 days of hospital admission, and 6‐month mortality. Results: Men had more impaired cognitive scores on 3MS, MMSE, HVOT, and Trails A ( P < .05) at baseline. These statistically significant differences between men and women remained on MMSE and HVOT after controlling for pre‐fracture dementia, in‐hospital delirium, age, education, race, and comorbidity. Men had higher 6‐month mortality rates (HR = 4.4, P < .001). Cognitive measures were also significantly associated with mortality, including 3MS, HVOT, and Trails B. Among the cognitive measures, higher 3MS was most protective for mortality (HR = 0.98, P < .001), both unadjusted and adjusted for other cognitive scales, comorbidity, delirium, and pre‐existing dementia. The highest mortality was among men with 3MS<78, with 26.3% dying within 6 months. The effects of cognition on mortality did not differ by sex. Conclusion: Men display greater levels of cognitive impairment within the first 22 days of hip fracture than women, and cognitive limitations increase the risk of mortality in both men and women.